Sharing Business Data Securely: Insights from the European Gaia-X Project on Technical and Economic Roles Enabling Federated Data Spaces - Heinbach, Christoph; Gessler, Jens; Rychlik, Hanspeter; Stecenko, Christine; Wieker, Horst; Schulz, Wolfgang H. (Journal of Telecommunications and the Digital Economy, 2024)
Federated data spaces (FDSs) represent an innovative approach to foster sovereign and interoperable data sharing across various business domains, promising substantial opportunities for value creation. The European Gaia-X initiative has emerged as a key driver in promoting FDS developments, particularly through its emphasis on data sovereignty and collaborative innovation. Effective design and operation of FDSs require a wide array of skills, expertise, services and technological components, creating a complex landscape for participating organisations. In this paper, we explore the technical and economic roles necessary for the successful implementation of FDSs, focusing on insights derived from two mobility use cases. Through interviews with experts engaged in a Gaia-X project, we identify 39 distinct roles, which we further abstract into eight meta-roles. These roles illustrate the structure and dynamics of inter-organisational collaboration in FDSs. Our analysis contributes to existing knowledge by illuminating the inter-organisational networks in FDSs, with a specific focus on the roles that support technical integration and economic value generation.